Development of power weeder for mound-cassava in hilly terrain - SELVAN, M MUTHAMIL; ANNAMALAI, S J K; RAVINDRAN, C S; SHERIFF, J T (The Indian Journal of Agricultural Sciences, 2015)
A power-weeder has been developed to address the weeding requirement of the cassava planted in mound pattern in hilly terrains. Although there are many commercial makes available for weeding of cassava planted in flat method as well as ridges and furrows method, it seems that there is no suitable weeder presently available in the country to address the weeding requirement of mound cassava of hilly terrains. The power weeder developed consists of petrolengine, main weeding rotor, offset weeding rotor, depth control lever, ground-wheels, transmission assembly, frame and handle. The main weeding rotor removes the weeds on the furrow while the offset weeding rotor removes the weeds on mounds without damaging the tuber grown under mounds. It is economically viable with fuel consumption limited to 27 L/ha. The machine proved its capability of weeding between the rows on both directions with acceptable weeding efficiency of 92.8% with negligible percentage (0.7) of damage to rhizome, field capacity of 0.16 ha/day, and field efficiency of 79.0%. It was also found that the operators did not observe any difficulty due to side thrust since the sideways thrust might have been transferred by the method of attaching the lateral rotor at 20mm ahead to the line joining central axis to the lateral axis. The power-weeder was recommended as an ideal machine for medium cassava farms of India.